The Basque Paradigm Shift: From Legislative Language Policies to Person-Centred Care - Montes Lasarte, Aitor; Arauzo, Xabier; Zarate Sesma, Jon (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
The Basque Country has two official languages, Basque and Spanish, the first being spoken by 37% of the population. The Basque Health Service has developed language schemes to fulfill the legal requirements. Currently, there is a vast transformational shift from legislative policies to an evidence-based, patient-centred care approach. This paper discusses three key issues which could enhance language appropriate care: the recording of patient’s preferred language; the Basque language care pathways as a suitable and effective approach for determining the language of service along the continuum of care; and bilingual electronic medical records, which bring to the fore the challenge of language barriers among professionals. Considering its bilingual human resources, it offers an opportunity for establishing compelling evidence about implementation.